Reporting of feasibility factors in publications on integrated treatment programs for women with substance abuse issues and their children: a systematic review and analysis - Henderson Joanna; Milligan Karen; Niccols Alison; Thabane Lehana; Sword Wendy; Smith Ainsley; Rosenkranz Susan (BMC, 2012)
Abstract Background Implementation of evidence-based practices in real-world settings is a complex process impacted by many factors, including intervention, dissemination, service provider, and organizational characteristics. Efforts to improve knowledge translation have resulted in greater attention to these factors. Researcher attention to the applicability of findings to applied settings also has increased. Much less attention, however, has been paid to intervention feasibility, an issue important to applied settings. Methods In a systematic review of 121documents regarding integrated treatment programs for women with substance abuse issues and their children, we examined the presence of feasibility-related information. Specifically, we analysed study descriptions for information regarding feasibility factors in six domains (intervention, practitioner, client, service delivery, organizational, and service system). Results On average, fewer than half of the 25 feasibility details assessed were included in the documents. Most documents included some information describing the participating clients, the services offered as part of the intervention, the location of services, and the expected length of stay or number of sessions. Only approximately half of the documents included specific information about the treatment model. Few documents indicated whether the intervention was manualized or whether the intervention was preceded by a standardized screening or assessment process. Very few provided information about the core intervention features versus the features open to local adaptation, or the staff experience or training required to deliver the intervention. Conclusions As has been found in reviews of intervention studies in other fields, our findings revealed that most documents provide some client and intervention information, but few documents provided sufficient information to fully evaluate feasibility. We consider possible explanations for the paucity of feasibility information and provide suggestions for better reporting to promote diffusion of evidence-based practices.